A new design method for stiffened plate based on topology optimization with min-max length-scale control - Wang, Shitao; Zhang, Haibing (Frontiers in Materials, 2023)
Stiffened plates are widely used in engineering due to their excellent manufacturing and mechanical properties. This paper introduces a novel method for designing stiffener plates that combines the H-DGTP formulation, robust topology optimization formulation, and maximum length-scale control. In comparison to existing methods, the proposed approach not only provides a clear layout of stiffeners but also optimizes their height. Sensitivity analysis of all design variables is derived for utilization with gradient-based optimizers. The study demonstrates that the implementation of the robust filter approach enables precise control of both structural features and gap widths, effectively avoiding sharp angles. Moreover, as the maximum length approaches the minimum length, the stiffeners assume uniform thickness, which better meets engineering requirements.Numerical examples are presented to validate the effectiveness of the proposed method.